Resin composition and molded article

By rationally formulating core-shell elastomer and silicone in polyacetal resin, the problem of deterioration of the welding elongation of polyacetal resin molded products is solved, and excellent performance of softness, slidingness and welding elongation is achieved. , improves the overall performance of molded products.

CN119317666APending Publication Date: 2025-01-14GLOBAL POLYACETAL CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202380045062.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-09
Filing Date
2023-06-02
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

After the existing polyacetal resin is combined with elastomer and silicone, the welding elongation of the molded product becomes worse, resulting in a decrease in strength, making it difficult to achieve excellent properties of softness, slippage and welding elongation at the same time.

Method used

Add core-shell elastomers of a specific average secondary particle size and silicones with a given kinetic viscosity to the polyacetal resin, adjusting their proportion and crosslinking index to improve welding elongation while maintaining softness and sliding sex.

Benefits of technology

Excellent properties of softness, sliding properties and welding elongation are achieved, ensuring high strength and good performance of molded products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005171113000000111
    Figure BDA0005171113000000111
  • Figure BDA0005171113000000161
    Figure BDA0005171113000000161
  • Figure BDA0005171113000000171
    Figure BDA0005171113000000171
Patent Text Reader

Abstract

Provided are: a resin composition which is capable of providing a molded article having excellent softness, excellent sliding properties, and excellent weld elongation at a moderate level; and a molded article formed from the resin composition. The resin composition contains a polyacetal resin (A), a core-shell elastomer (B), and a silicone (C), the average secondary particle diameter of the core-shell elastomer (B) in the polyacetal resin (A) being 10-250 nm, the content of the core-shell elastomer (B) in the resin composition being 5-25 mass%, and the kinematic viscosity of the silicone (C) at 25 DEG C being 4 million-30 million cSt, and the content of the silicone (C) in the resin composition being 0.3-1 mass%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a resin composition and a molded product, and particularly to a resin composition containing a polyacetal resin as a main component. Background Art

[0002] Polyacetal resin is a plastic with excellent mechanical properties, electrical properties, chemical resistance and other chemical properties, and has been used in a wide range of applications.

[0003] Here, in order to make the polyacetal resin soft, the addition of an elastomer was studied.

[0004] For example, Patent Document 1 describes a resin composition comprising a polyacetal resin and a core-shell elastomer, wherein the resin composition is molded into a multi-purpose test piece having a thickness of 4 mm, and the flexural modulus measured in accordance with ISO178 is 1700 MPa or less, and the resin composition is molded into a test piece having a thickness of 1.6 mm and having a weld portion in the center, and the weld elongation when stretched at 10 mm / min in accordance with ASTM D638 is 20% or more.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent Application Publication No. 2021-011562 Summary of the invention

[0008] Problems to be solved by the invention

[0009] The molded article obtained from the resin composition containing a polyacetal resin and an elastomer described in Patent Document 1 has excellent softness. On the other hand, as the use of polyacetal resins has expanded in recent years, resin compositions that can produce molded articles that have softness and excellent sliding properties are required.

[0010] Here, in order to improve the sliding property, it is considered to mix silicone in polyacetal resin. However, if an elastomer or silicone is mixed in polyacetal resin, there is a tendency that the weld elongation of the obtained molded product will be poor. If the weld elongation is poor, the strength of the molded product will be reduced.

[0011] The present invention aims to solve the above-mentioned problems, and its object is to provide a resin composition capable of obtaining a molded product having moderately excellent softness, excellent slidability, and excellent weld elongation, and a molded product formed from the resin composition.

[0012] Solutions to the problem

[0013] The present inventors have conducted studies based on the above problems and found that the above problems can be solved by adding a core-shell elastomer having a given average secondary particle size in the polyacetal resin and a silicone having a given kinematic viscosity in a given amount to the polyacetal resin.

[0014] Specifically, the above problems can be solved by the following methods.

[0015] <1> A resin composition comprising a polyacetal resin (A), a core-shell elastomer (B), and silicone (C),

[0016] In the polyacetal resin (A), the average secondary particle size of the core-shell elastomer (B) is 10 to 250 nm.

[0017] In the resin composition, the content of the core-shell elastomer (B) is 5 to 25% by mass.

[0018] The kinematic viscosity of the silicone (C) at 25° C. is 4 to 30 million cSt, and the content of the silicone (C) in the resin composition is 0.3 to 1% by mass.

[0019] <2> The resin composition according to <1>, wherein

[0020] The crosslinking index of the core-shell elastomer (B) is in the range of 0.11 to 0.30.

[0021] <3> The resin composition according to <1> or <2>, wherein

[0022] In the above core-shell elastomer (B), the core comprises a butadiene-containing rubber, and the shell comprises an acrylic resin.

[0023] <4> The resin composition according to any one of <1> to <3>, further comprising a hydrazide compound and / or a urea compound.

[0024] <5> The resin composition according to any one of <1> to <4>, wherein

[0025] The mass ratio (B) / (C) of the core-shell elastomer (B) to the silicone (C) is 8-40.

[0026] <6> The resin composition according to any one of <1> to <5>, which is a resin composition for trim clip molding.

[0027] <7> The resin composition according to <1>, wherein

[0028] The crosslinking index of the core-shell elastomer (B) is in the range of 0.11 to 0.30.

[0029] In the core-shell elastomer (B), the core comprises a butadiene-containing rubber, the shell comprises an acrylic resin,

[0030] The resin composition further comprises a hydrazide compound and / or a urea compound,

[0031] The mass ratio (B) / (C) of the core-shell elastomer (B) to the silicone (C) is 8 to 40.

[0032] The resin composition is a resin composition for clip molding of decorative parts.

[0033] <8> Pellets comprising the resin composition according to any one of <1> to <7>.

[0034] <9> A molded article formed from the resin composition according to any one of <1> to <7>.

[0035] <10> A molded article formed from the pellets according to <8>.

[0036] <11> The molded article according to <9>, which is a decorative buckle.

[0037] Effects of the Invention

[0038] According to the present invention, there can be provided a resin composition capable of obtaining a molded article having moderately excellent softness, excellent slidability, and excellent weld elongation, and a molded article formed from the resin composition. DETAILED DESCRIPTION

[0039] Hereinafter, a mode for implementing the present invention (hereinafter, simply referred to as "this embodiment") will be described in detail. It should be noted that the following this embodiment is an example for describing the present invention, and the present invention is not limited to this embodiment.

[0040] In addition, in this specification, "to" is used to mean that the numerical values ​​described before and after it are included as a lower limit and an upper limit.

[0041] In this specification, various physical property values ​​and characteristic values ​​are values ​​at 23°C unless otherwise specified.

[0042] The measurement methods and the like described in the standards shown in this specification may differ depending on the year, but unless otherwise specified, they are based on the standards as of January 1, 2022.

[0043] The resin composition of the present embodiment comprises a polyacetal resin (A), a core-shell elastomer (B), and silicone (C), wherein the average secondary particle size of the core-shell elastomer (B) in the polyacetal resin (A) is 10 to 250 nm, the content of the core-shell elastomer (B) in the resin composition is 5 to 25% by mass, and the kinematic viscosity of the silicone (C) at 25° C. is 4 to 30 million cSt, and the content of the silicone (C) in the resin composition is 0.3 to 1% by mass. By using such a resin composition, a resin composition capable of obtaining a molded product having excellent softness, excellent sliding properties, and excellent weld elongation can be obtained.

[0044] When an elastomer is added to the polyacetal resin (A), the softness of the resulting molded product tends to be improved. On the other hand, when silicone is added, the sliding property tends to be improved. However, if an elastomer or silicone is added to the polyacetal resin (A), the weld elongation tends to be poor. In the present invention, in order to solve the above-mentioned problems, a core-shell elastomer (B) having an average secondary particle size of 10 to 250 nm is added to the polyacetal resin (A) as an elastomer. It can be inferred that by setting the average secondary particle size of the core-shell elastomer (B) to a given range, the force applied to the interface between the core-shell elastomer (B) and the polyacetal resin (A) is reduced, and the weld elongation can be improved. In addition, it can be inferred that by using a silicone with a given kinematic viscosity as the silicone (C) in a given amount, the reduction in weld elongation can be effectively suppressed while maintaining the sliding property.

[0045] <Polyacetal resin (A)>

[0046] The resin composition (A) of the present embodiment contains a polyacetal resin.

[0047] The polyacetal resin is not particularly limited and may be a homopolymer containing only a divalent oxymethylene group as a structural unit, or a copolymer containing a divalent oxymethylene group and a divalent oxyalkylene group having 2 to 6 carbon atoms as structural units.

[0048] Examples of the oxyalkylene group having 2 to 6 carbon atoms include oxyethylene group, oxypropylene group, and oxybutylene group.

[0049] In the polyacetal resin, the ratio of the oxyalkylene group having 2 to 6 carbon atoms to the total molar number of the oxymethylene group and the oxyalkylene group having 2 to 6 carbon atoms is not particularly limited and may be 0.5 to 10 mol %.

[0050] In order to produce the above-mentioned polyacetal resin, three In order to introduce an oxyalkylene group having 2 to 6 carbon atoms into the polyacetal resin, a cyclic formal or a cyclic ether can be used. Specific examples of cyclic formals include 1,3-dioxolane, 1,3-dioxolane, Examples of the cyclic ethers include 1,3-dioxolane, 1,3-dioxolane, 1,3,5-trioxolane, 1,3,6-trioxolane, etc. Specific examples of the cyclic ethers include ethylene oxide, propylene oxide, and butylene oxide. To introduce ethylene oxide into the polyacetal resin, 1,3-dioxolane can be used as the main raw material. To introduce propylene oxide, 1,3-dioxolane can be used as the main raw material. In order to introduce oxybutylene groups, 1,3-dioxepane can be used as the main raw material. It should be noted that in the polyacetal resin, it is preferred that the amount of hemiformal terminal groups, formyl terminal groups, and terminal groups unstable to heat, acid, and alkali are small. Here, the hemiformal terminal group refers to a group represented by -OCH2OH, and the formyl terminal group refers to a group represented by -CHO.

[0051] As the polyacetal resin, in addition to the above, the polyacetal resins described in paragraphs 0018 to 0043 of JP-A-2015-074724 may be used, and the contents thereof are incorporated herein.

[0052] The resin composition (A) of the present embodiment preferably contains 70% by mass or more of the polyacetal resin in the resin composition (A), more preferably 75% by mass or more, further preferably 80% by mass or more, and further preferably 85% by mass or more. The upper limit is preferably 95% by mass or less, more preferably 92% by mass or less.

[0053] The resin composition of the present embodiment may contain only one polyacetal resin or two or more polyacetal resins. When containing two or more polyacetal resins, the total amount is preferably within the above range.

[0054] <Core-shell elastomer (B)>

[0055] The resin composition of the present embodiment includes a core-shell elastomer (B). By using an elastomer, softness can be imparted to the obtained molded product. In addition, by using a core-shell elastomer as an elastomer, the reduction of weld elongation can be effectively suppressed. In addition, by adjusting the average secondary particle size of the core-shell elastomer (B) in the polyacetal resin (A) to 10 to 250 nm, the reduction of weld elongation can be effectively suppressed while keeping softness at a high level.

[0056] The core-shell elastomer is a polymer having a multilayer structure having a core and a shell layer covering part or all of the core, and known ones include Kane Ace series from Kaneka Corporation and Metablen series from Mitsubishi Chemical Corporation.

[0057] The average secondary particle size of the core-shell elastomer (B) is 10 to 250 nm in the polyacetal resin (A). By setting the average secondary particle size of the core-shell elastomer (B) to less than 250 nm, the core-shell elastomer (B) is easily dispersed in the polyacetal resin (A), and the weld elongation can be improved. This is because if the average secondary particle size of the core-shell elastomer (B) increases, the core-shell elastomer (B) will become the starting point of damage in the molded product. In addition, the force applied to the interface between the core-shell elastomer (B) and the polyacetal resin (A) is also reduced, which can improve the weld elongation. Such an average secondary particle size of the core-shell elastomer (B) in the polyacetal resin (A) can be achieved by adjusting the selection of the type of the core-shell elastomer (B), the fluidity of the polyacetal resin, the conditions of melt kneading, etc.

[0058] The average secondary particle size of the core-shell elastomer (B) is preferably 240 nm or less, more preferably 210 nm or less, further preferably 180 nm or less, further preferably 150 nm or less, and further preferably 120 nm or less. In addition, it is more preferably 30 nm or more, further preferably 50 nm or more, further preferably 80 nm or more, and further preferably 100 nm or more.

[0059] The average secondary particle size of the core-shell elastomer (B) can be measured according to the description in the Examples described below.

[0060] The crosslinking index of the core-shell elastomer (B) used in the present embodiment is preferably in the range of 0.11 to 0.30.

[0061] The crosslinking index of the core-shell elastomer (B) is more preferably more than 0.15, more preferably more than 0.19, and preferably less than 0.29, more preferably less than 0.28, and more preferably less than 0.27. The crosslinking index refers to the degree of intermolecular crosslinking of the core portion of the core-shell elastomer. That is, the larger the crosslinking index, the harder the elastomer is, and the smaller the crosslinking index, the softer the elastomer is. By setting the crosslinking index to more than the above lower limit, the weld elongation increases. It can be inferred that this is because the harder the elastomer is, the less it will deform due to the force applied to the weld during molding, and the more it can maintain its spherical shape. In addition, by setting the crosslinking index to less than the above upper limit, the impact absorption as the effect of the elastomer will not occur, and there is a tendency to more effectively exert impact resistance.

[0062] The crosslinking index of the core-shell elastomer (B) can be adjusted by, for example, the polymerization conditions during the production of the core-shell elastomer.

[0063] The crosslinking index of the core-shell elastomer (B) can be measured and calculated by the method described in Examples below.

[0064] The type of the core-shell elastomer (B) used in the present embodiment is not particularly limited, and the core is preferably a rubber polymer. As the rubber polymer, it is preferably selected from at least one of a butadiene-containing rubber, a butyl acrylate-containing rubber, a 2-ethylhexyl acrylate-containing rubber, and a silicone rubber, and more preferably a butadiene-containing rubber. The shell is preferably a polymer of one or more monomers selected from (meth)acrylates, aromatic vinyl compounds, etc., and more preferably a polymer (acrylic resin) in which the units derived from (meth)acrylates account for more than 50% by mass of the total.

[0065] In the core-shell elastomer (B) used in the present embodiment, it is preferred that the core contains a rubber-based polymer and the shell contains an acrylic resin. If such a core-shell elastomer is used, the effects of the present invention tend to be more effectively exhibited.

[0066] The resin composition of the present embodiment includes more than 5% by mass of core-shell elastomer (B), preferably more than 6% by mass, more preferably more than 7% by mass, and further preferably more than 8% by mass. By being set to more than the above-mentioned lower limit, there is a tendency that the softness of the obtained molded article is improved. The upper limit of the content of the above-mentioned core-shell elastomer (B) is less than 25% by mass, preferably less than 22% by mass, more preferably less than 18% by mass, more preferably less than 16% by mass, and can also be less than 14% by mass. By being set to less than the above-mentioned upper limit, softness and welding elongation can be improved with good balance.

[0067] The resin composition of the present embodiment may contain only one core-shell elastomer (B) or two or more thereof. When containing two or more thereof, the total amount is preferably within the above range.

[0068] <Silicone (C)>

[0069] The resin composition of the present embodiment contains silicone (C). By containing silicone (C), the slidability of the obtained molded article can be improved.

[0070] The kinematic viscosity of the organosilicon compound (C) used in the present embodiment at 25°C is 4 million cSt or more, preferably 7 million cSt or more, and more preferably 10 million cSt or more. By setting it to be above the above lower limit, there is a tendency that the limiting PV value is further improved. In addition, the kinematic viscosity of the above-mentioned organosilicon compound (C) at 25°C is 30 million cSt or less, preferably 28 million cSt or less, more preferably 25 million cSt or less, and further preferably 20 million cSt or less. By setting it to be below the above upper limit, there is a tendency that the dispersibility of the organosilicon (C) in the polyacetal resin is improved and the weld elongation is further improved.

[0071] The organosilicon compound (C) is not particularly limited, but is preferably polyorganosiloxane. Examples of the organic group that the polyorganosiloxane may have include alkyl groups having 2 to 20 carbon atoms, phenyl groups, halogenated phenyl groups, silicone-containing groups, epoxy groups, amino groups, alcoholic hydroxyl groups, and polyether groups.

[0072] In this embodiment, the organosilicon compound (C) is preferably silicone gum.

[0073] The content of the organosilicon (C) in the resin composition of the present embodiment is preferably 0.3% by mass or more, more preferably 0.4% by mass or more in the resin composition. By setting it to above the above lower limit, the sliding property can be improved. In addition, in the resin composition, the upper limit of the content of the above-mentioned organosilicon (C) is 1% by mass or less, preferably 0.9% by mass or less, more preferably 0.8% by mass or less, further preferably 0.7% by mass or less, and further preferably 0.6% by mass or less. By setting it to below the above upper limit, the welding elongation can be maintained at a high level.

[0074] The resin composition of the present embodiment may contain only one type of silicone (C) or two or more types. When containing two or more types, the total amount is preferably within the above range.

[0075] In the resin composition of the present embodiment, the total amount of the polyacetal resin (A), the core-shell elastomer (B), and the silicone (C) preferably accounts for 96% by mass or more of the resin composition, more preferably 97% by mass or more, further preferably 98% by mass or more, and may also account for 99% by mass or more. However, the total amount of the polyacetal resin (A), the core-shell elastomer (B), and the silicone (C) does not exceed 100% by mass.

[0076] In addition, in the resin composition of the present embodiment, the mass ratio of the core-shell elastomer (B) to the silicone (C), i.e., (B) / (C), is preferably 8 or more, more preferably 9 or more, and even more preferably 10 or more. By setting it to be equal to or more than the above lower limit, there is a tendency that the weld elongation is further improved. In addition, the above (B) / (C) is preferably 40 or less, more preferably 35 or less, even more preferably 32 or less, even more preferably 30 or less, and even more preferably 25 or less. By setting it to be equal to or less than the above upper limit, there is a tendency that the sliding property is further improved.

[0077] <Formaldehyde scavenger>

[0078] The resin composition of the present embodiment may contain a formaldehyde scavenger. By containing the formaldehyde scavenger, the generation of formaldehyde from the obtained molded article can be effectively suppressed.

[0079] The formaldehyde scavenger preferably contains at least one selected from the group consisting of a hydrazide compound, a hydrazine compound hydrazone, a guanamine compound, and a urea compound, and more preferably a hydrazide compound and / or a urea compound.

[0080] For details of these formaldehyde scavengers, reference can be made to paragraphs 0021 to 0036 of JP-A-2020-132662, the contents of which are incorporated herein.

[0081] In the resin composition of the present embodiment, the formaldehyde scavenger is preferably contained in an amount of 0.05 parts by mass or more, more preferably 0.10 parts by mass, relative to 100 parts by mass of the polyacetal resin (A). In addition, the formaldehyde scavenger is preferably contained in an amount of 0.5 parts by mass or less, more preferably 0.3 parts by mass or less, relative to 100 parts by mass of the polyacetal resin.

[0082] The resin composition of the present embodiment may contain only one formaldehyde scavenger or may contain two or more. When containing two or more, the total amount is within the above range.

[0083] <Other ingredients>

[0084] The resin composition of the present embodiment may include any known additives and fillers within the scope of not damaging the purpose of the present invention. As additives and fillers used in the present embodiment, for example, thermoplastic resins other than polyacetal resins, ultraviolet absorbers, antioxidants, heat stabilizers, stabilizers, formaldehyde scavengers, antistatic agents, carbon fibers, dyes, organic pigments such as carbon black, inorganic pigments such as titanium oxide, glass fibers, glass flakes, potassium titanate whiskers, etc. can be cited. Their details can refer to the records of paragraphs 0113 to 0124 of Japanese Patent Publication No. 2017-025257, and their contents are introduced into this specification.

[0085] <Physical properties of resin composition>

[0086] The resin composition of the present embodiment preferably has excellent weld elongation and does not break before yield. Specifically, the resin composition of the present embodiment is molded into an ASTM tensile test piece (thickness 1.6 mm), and the weld elongation during the tensile test according to ASTM D638 is preferably 14% or more, more preferably 17% or more, further preferably 18% or more, and further preferably 20% or more. In addition, the upper limit of the above-mentioned weld elongation is, for example, 300% or less.

[0087] For the resin composition (A) of this embodiment, the above-mentioned resin composition (A) is molded into a multi-purpose test piece (ISO test piece) with a thickness of 4 mm, and the bending elastic modulus measured according to ISO178 is preferably greater than 1000 MPa, more preferably greater than 1500 MPa, and is also preferably less than 3000 MPa, more preferably less than 2500 MPa.

[0088] In the present embodiment, by setting the above range, a molded product having appropriate softness can be obtained.

[0089] The above bending elastic modulus is mainly achieved by combining the core elastic body.

[0090] <Method for producing resin composition>

[0091] The resin composition of the present embodiment contains the above-mentioned essential components and the above-mentioned optional components used as needed. Moreover, the manufacturing method thereof can select any method so that the average secondary particle size reaches the above-mentioned range. The manufacturing method of any resin composition known in the art can be used to mix / knead these raw materials.

[0092] As one of the methods for making the average secondary particle size within the above range, there can be cited a method in which a polyacetal resin and a core-shell elastomer are mixed with a roller, extruded through a melt-kneading machine, and cut into strands to form particles. At this time, as a melt-kneading machine, a twin-screw extruder is preferably used from the aspect that secondary coagulation is easy to occur in the case of a single-screw extruder. Among them, the ratio of the length L (mm) of the screw to the diameter D (mm) of the screw, i.e., L / D, is preferably 20 or more, more preferably 30 or more, and preferably 100 or less, more preferably 70 or less. By setting the above L / D to 20 or more, the core-shell elastomer is easily micro-dispersed, and the secondary coagulation of the core-shell elastomer can be effectively suppressed. In addition, by setting the above L / D to 100 or less, there is a tendency to effectively suppress the discoloration of the resin composition caused by thermal degradation.

[0093] The shape of the die nozzle is not particularly limited. From the perspective of particle shape, a circular nozzle with a diameter of 1 mm or more is preferred, and a circular nozzle with a diameter of 2 mm or more is more preferred. A circular nozzle with a diameter of 10 mm or less is also preferred, and a circular nozzle with a diameter of 7 mm or less is more preferred.

[0094] In addition, the melting temperature of the resin composition during melt kneading is preferably 170° C. or higher, more preferably 190° C. or higher, and preferably 250° C. or lower, more preferably 230° C. or lower. By setting the melting temperature to 170° C. or higher, there is a tendency that melting becomes sufficient and production volume is improved. In addition, by setting it to 250° C. or lower, there is a tendency that discoloration of the resin composition caused by thermal degradation can be effectively suppressed.

[0095] The screw structure of the twin-screw extruder is not particularly limited, and one of the preferred embodiments is to have at least two kneading sections. The kneading section has a kneading disk, which mainly contributes to the melting of the resin and the dispersion of the elastomer.

[0096] The screw speed during melt kneading is preferably 50 rpm or more, more preferably 70 rpm or more, and preferably 500 rpm or less, more preferably 350 rpm or less. By setting the screw speed to 50 rpm or more, the core-shell elastomer is easily micro-dispersed, and there is a tendency to more effectively suppress the occurrence of secondary agglomeration. In addition, by setting it to 500 rpm or less, the heat generated during melt kneading can be suppressed, and there is a tendency to effectively suppress the discoloration of the resin composition caused by thermal degradation. In addition, the ejection amount is preferably 5 kg / hr or more, more preferably 7 kg / hr or more, preferably 1000 kg / hr or less, and more preferably 800 kg / hr or less. By setting it to 5 kg / hr or more, the core-shell elastomer is more easily micro-dispersed, and the occurrence of secondary agglomeration can be effectively suppressed. In addition, by setting it to 1000 kg / hr or less, the heat generated during melt kneading can be effectively suppressed, and there is a tendency to effectively suppress the discoloration of the resin composition caused by thermal degradation.

[0097] The ratio (Q / Ns) of the screw speed (Ns) to the discharge amount (Q) during melt kneading also depends on the screw diameter and screw structure of the extruder, and is, for example, preferably 0.5 or more, more preferably 0.7 or more, particularly preferably 0.9 or more, and preferably 1.5 or less, more preferably 1.3 or less, particularly preferably 1.2 or less. The above Q / Ns is particularly preferred in an embodiment in which the screw diameter is 18 to 75 mm (further 58 mm) and has two kneading sections as the screw structure.

[0098] Examples of the mixer include a kneader, a Banbury mixer, an extruder, etc. There are no particular restrictions on the various conditions and devices for mixing / kneading, and they can be appropriately selected and determined from any known conditions. Kneading is preferably carried out at a temperature above the melting temperature of the polyacetal resin, specifically above the melting temperature of the polyacetal resin (generally above 180° C.).

[0099] <Molding products>

[0100] The molded article of the present embodiment is formed from the resin composition of the present embodiment. The resin composition of the present embodiment is usually injection molded as it is or by pelletizing the pellets to produce a molded article.

[0101] That is, a preferred example of the molded product of the present embodiment is an injection molded product. An injection molded product is a molded product obtained by injection molding, and generally, a weak portion (weld portion) is formed at a portion where molten resins merge in a mold.

[0102] The shape of the molded product is not particularly limited and can be appropriately selected according to the use and purpose of the molded product, and examples thereof include: plate-shaped, disk-shaped, rod-shaped, sheet-shaped, film-shaped, cylindrical, ring-shaped, circular, elliptical, gear-shaped, polygonal, special-shaped, hollow, frame-shaped, box-shaped, panel-shaped, cap-shaped, etc. The molded product of the present invention can be a component or a finished product.

[0103] <Application>

[0104] Examples of the resin composition of the present embodiment and molded articles formed from the resin composition include automotive parts such as decorative buckles, seat belt components, and headrest rails, building material parts, electrical / electronic parts, commercial equipment parts, daily necessities parts, and containers for frozen foods, beverages, etc., household appliances such as refrigerator gaskets, hose clamps, packaging, and strapping tapes.

[0105] In particular, the resin composition and the molded article of the present embodiment are suitable for decorative clips.

[0106] Example

[0107] Below, give embodiment and the present invention is described more specifically.As long as do not depart from the gist of the present invention, the material, dosage, ratio, processing content, processing steps etc. shown in the following embodiment can be appropriately changed.Therefore, the scope of the present invention is not limited to the specific example shown below.

[0108] When the measuring equipment used in the examples is difficult to obtain due to discontinuation of production or the like, other equipment having equivalent performance may be used for measurement.

[0109] 1. Raw materials

[0110] The raw materials shown in the following Table 1 were used.

[0111] [Table 1]

[0112]

[0113] The above MVR is the melt volume flow rate measured under the conditions of a temperature of 190° C. and a load of 2.16 kg according to ISO1133.

[0114] The kinematic viscosities of the silicone oil and raw silicone rubber are values ​​measured by the following method.

[0115] (i) 1.0 g of silicone oil or silicone rubber was weighed and dissolved in 10 mL of toluene, and the viscosity of the silicone-toluene solution was measured using a cone-plate viscometer TPE100.

[0116] (ii) The viscosity of silicone oil with known kinematic viscosity was measured by the same method to prepare a calibration curve.

[0117] (iii) Calculate the kinematic viscosity of silicone oil or silicone rubber by extrapolation using the calibration curve.

[0118] <Core-shell elastomer crosslinking index>

[0119] For each core-shell elastomer used in each embodiment and comparative example, the T2 relaxation time was measured using Minispecmq20 manufactured by Bruker. The measurement was carried out at -40°C, 0°C, 23°C, and 80°C, and each T2 relaxation time was obtained. Regarding the approximate straight line of the curve obtained when the measurement temperature is used as the X-axis and the T2 relaxation time is used as the Y-axis, it can be considered that the larger the slope, the higher the molecular mobility, that is, the fewer cross-linked structures that restrict the movement of the molecules, and the smaller the slope, the lower the molecular mobility, that is, the more cross-linked structures that restrict the movement of the molecules. The inverse of the slope of the above approximate straight line is taken as the cross-linking index. The measurement temperatures of -40°C and 0°C are assumed by the Solid echo method, and the measurement temperatures of 23°C and 80°C are measured by the Spin echo method.

[0120] The T2 relaxation time was measured under the following conditions.

[0121] Observation frequency: 25MHz

[0122] Measurement method: Solid echo method / Spin echo method

[0123] Repeat time: 4sec / 4sec

[0124] Number of points: 16 times / 4 times

[0125] Measuring temperature: -40℃, 0℃ / 23℃, 80℃

[0126] 2. Examples 1 to 14, Comparative Examples 1 to 9, Reference Examples 1 to 3

[0127] <Production of resin composition (pellets)>

[0128] Using a super mixer manufactured by Kawada Manufacturing Co., Ltd., the components shown in Tables 2 to 6 were uniformly mixed in the ratios (parts by mass) shown in Tables 2 to 6. The obtained mixture was melt-shear mixed using a twin-screw extruder with a screw diameter of 30 mm, a screw length of 760, and a die nozzle diameter of 3.5 mm ("PCM-30" manufactured by Ikegai Co., Ltd.) at a barrel temperature of 200° C., a screw speed of 120 rpm, and a discharge amount of 10 kg / hour to produce pellets of the resin composition.

[0129] <Average secondary particle size of core-shell elastomer (nm)>

[0130] The pellets obtained above were heat-treated in a hot air circulation dryer at a temperature of 80° C. for 4 hours.

[0131] Next, the dried pellets were subjected to an injection molding machine with the cylinder temperature set to 195° C. and the mold temperature set to 90° C. to prepare an ASTM tensile test piece (thickness 3.2 mm) having a welded portion at the center.

[0132] A test piece for observation under a scanning electron microscope (SEM) was cut out from the ASTM tensile test piece using a diamond knife in parallel with the flow direction during molding and including the welded portion.

[0133] After osmium tetroxide was vapor-deposited on the observation surface of the obtained test piece for SEM observation, a SEM image was obtained using a scanning electron microscope (SEM).

[0134] Based on the obtained SEM images, the average value of the maximum lengths of the island-like portions derived from the elastomer was taken as the average secondary particle size of the elastomer.

[0135] The injection molding machine used was EC-100S manufactured by Shibaura Machine Co., Ltd.

[0136] Osmium tetroxide was deposited at 8 mA for 60 seconds using an "Osmium Coater" manufactured by MEIWAFOSIS. Scanning electron microscopy was performed using a "Scanning Electron Microscope (SEM) S-4800" manufactured by Hitachi High-Tech, and SEM images were obtained under the conditions of acceleration voltage: 1 kV, signal: LA100 (U), emission current: 6 μA, and detection current: Normal.

[0137] <Welding elongation>

[0138] The pellets obtained above were heat-treated in a hot air circulation dryer at a temperature of 80° C. for 4 hours.

[0139] Next, an ASTM tensile test piece (thickness 1.6 mm) having a weld portion in the center was prepared using an injection molding machine with the barrel temperature set to 195°C and the mold temperature set to 90°C. A tensile test was performed according to ASTM D638, and the weld elongation was measured.

[0140] The injection molding machine used was EC-100S manufactured by Shibaura Machine Co., Ltd.

[0141] The unit is expressed in %. The measurement results were evaluated according to the following criteria.

[0142] A: More than 14%

[0143] B: 10% or more and less than 14%

[0144] C: less than 10%

[0145] The results are shown in Tables 2 to 6 below.

[0146] <Dynamic friction coefficient>

[0147] The pellets obtained above were heat-treated in a hot air circulation dryer at a temperature of 80° C. for 4 hours.

[0148] Next, the dried pellets were subjected to an injection molding machine with the cylinder temperature set at 195°C and the mold temperature set at 80°C to produce a cylindrical thrust test piece with a contact area of ​​2 cm. 2 The test piece was tested using a Suzuki friction and wear tester at a temperature of 23°C and a humidity of 50% with a load of 10 kgf and a linear speed of 10 cm / s between the same materials to obtain the dynamic friction coefficient (μ). The test results were evaluated according to the following criteria.

[0149] A: less than 0.32

[0150] B: 0.32 or more and less than 0.34

[0151] C: 0.34 or above

[0152] The results are shown in Tables 2 to 6 below.

[0153] <Relative wear amount>

[0154] The pellets obtained above were heat-treated in a hot air circulation dryer at a temperature of 80° C. for 4 hours.

[0155] Next, the dried pellets were subjected to an injection molding machine with the cylinder temperature set at 195°C and the mold temperature set at 80°C to produce a cylindrical thrust test piece with a contact area of ​​2 cm. 2 The test piece was tested using a Suzuki-type friction and wear tester at a temperature of 23°C and a humidity of 50% with a load of 3 kgf and a linear speed of 30 cm / s between the same materials for 20 hours. The relative wear amount was calculated based on the mass of the cylindrical thrust test piece before and after the test. The relative wear amount is the sum of the relative wear amounts of the two test pieces used in the wear test.

[0156] The unit is ×10 -2 (mm 3 / kgf·km).

[0157] In addition, the measurement results were evaluated according to the following criteria.

[0158] A: less than 20×10 -2 (mm 3 / kgf·km)

[0159] B: 20×10 -2 (mm 3 / kgf·km) and less than 30×10 -2 (mm 3 / kgf·km)

[0160] C: 30×10 -2 (mm 3 / kgf·km) or above

[0161] The results are shown in Tables 2 to 6 below.

[0162] <Flexural modulus>

[0163] The pellets obtained above were heat-treated in a hot air circulation dryer at a temperature of 80° C. for 4 hours.

[0164] Next, the dried pellets were injection molded using an injection molding machine with the barrel temperature set to 195°C and the mold temperature set to 90°C in accordance with ISO9988-2. The injection molding machine used was EC-100S manufactured by Shibaura Machine Co., Ltd. Thus, a 4 mm thick multi-purpose test piece (ISO test piece) was obtained.

[0165] Next, for the multi-purpose test piece (ISO test piece) with a thickness of 4 mm, a bending test was performed at a bending test speed of 2 mm / min using a fully automatic bending tester as a bending tester according to the method described in ISO178, and the bending elastic modulus was measured. The fully automatic bending tester used was a fully automatic bending tester manufactured by Shimadzu Corporation. The unit is expressed in MPa. The evaluation criteria are as follows.

[0166] A: 1500MPa or more and less than 2400MPa

[0167] B: 1300MPa or more and less than 1500MPa or 2400MPa or more and less than 2450MPa

[0168] C: less than 1300MPa or more than 2450MPa

[0169] The results are shown in Tables 2 to 6 below.

[0170] <Formaldehyde generation>

[0171] The pellets obtained above were heat-treated in a hot air circulation dryer at a temperature of 80° C. for 4 hours.

[0172] Next, the dried pellets were used to prepare a 100 mm × 40 mm × 2 mm flat test piece using an injection molding machine with the barrel temperature set to 210° C. and the mold temperature set to 80° C. For the test piece, the formaldehyde generation amount in 1 g of the polyacetal resin was measured by the following method according to the method described in the German Association of the Automotive Industry standard VDA275 (Automotive interior parts - Quantification of formaldehyde emission based on the revised flask method).

[0173] (i) 50 mL of distilled water was added to the polyethylene container, and the flat test piece was hung in the air with the lid closed. The container was then heated at 60° C. for 3 hours in a sealed state.

[0174] (ii) After leaving the plate at room temperature for 60 minutes, the plate test piece was taken out.

[0175] (iii) The amount of formaldehyde absorbed in the distilled water in the polyethylene container was measured by the acetylacetone colorimetric method using a UV spectrometer, and the value obtained by dividing the amount of formaldehyde by the mass of POM in the flat test piece was taken as the amount of formaldehyde generated.

[0176] The unit is expressed as the amount of formaldehyde generated per 1 g of the polyacetal resin (μg), that is, μg / g-POM. The measurement results were evaluated according to the following criteria.

[0177] A: Less than 5μg / g-POM

[0178] B: 5μg / g-POM or more and less than 10μg / g-POM

[0179] C: 10μg / g-POM or above

[0180] The results are shown in Tables 2 to 6 below.

[0181] <Overall Evaluation>

[0182] Among the evaluation results of the above-mentioned weld elongation, dynamic friction coefficient, relative wear amount, bending elastic modulus, and formaldehyde generation amount, the worst result was used as the comprehensive evaluation.

[0183] The results are shown in Tables 2 to 6.

[0184] [Table 2]

[0185]

[0186] [Table 3]

[0187]

[0188] [Table 4]

[0189]

[0190] [Table 5]

[0191]

[0192] [Table 6]

[0193]

[0194] As is clear from Tables 2 to 6 above, the resin composition of the present invention is excellent in sliding property and also excellent in wear resistance (Examples 1 to 14).

[0195] In contrast, when the average secondary particle size of the core-shell elastomer (B) in the polyacetal resin (A) was large (Comparative Examples 1 and 2), the weld elongation was small or a resin composition (pellet) could not be obtained.

[0196] When the content of the core-shell elastomer (B) was small (Comparative Example 3), the elastic modulus was high, whereas when the content was too large (Comparative Example 4), the elastic modulus was too low. In either case, appropriate softness could not be maintained.

[0197] In addition, when the content of the organosilicon compound (C) was too large (Comparative Examples 5 and 7), the weld elongation was low, and in addition, when the content was too large (Comparative Example 6), the sliding property was poor.

[0198] Furthermore, when the kinematic viscosity of the organosilicon compound (C) was low (Comparative Examples 8 and 9), the sliding property was poor.

[0199] In addition, when a slip improving agent other than the organosilicon compound (C) was used (Reference Examples 1 to 3), the slip was insufficient or formaldehyde was generated.

Claims

1. A resin composition comprising a polyacetal resin (A), a core-shell elastomer (B), and silicone (C), In the polyacetal resin (A), the average secondary particle size of the core-shell elastomer (B) is 10 to 250 nm. In the resin composition, the content of the core-shell elastomer (B) is 5 to 25% by mass. The kinematic viscosity of the silicone (C) at 25° C. is 4 to 30 million cSt, and the content of the silicone (C) in the resin composition is 0.3 to 1% by mass.

2. The resin composition according to claim 1, wherein The crosslinking index of the core-shell elastomer (B) is in the range of 0.11 to 0.

30.

3. The resin composition according to claim 1 or 2, wherein In the core-shell elastomer (B), the core comprises a butadiene-containing rubber, and the shell comprises an acrylic resin. The resin composition according to claim 1 or 2, further comprising a hydrazide compound and / or a urea compound.

5. The resin composition according to claim 1 or 2, wherein The mass ratio (B) / (C) of the core-shell elastomer (B) to the silicone (C) is 8-40. The resin composition according to claim 1 or 2, which is a resin composition for clip molding of decorative parts.

7. The resin composition according to claim 1, wherein The crosslinking index of the core-shell elastomer (B) is in the range of 0.11 to 0.30, In the core-shell elastomer (B), the core comprises a butadiene-containing rubber, the shell comprises an acrylic resin, The resin composition further comprises a hydrazide compound and / or a urea compound, The mass ratio (B) / (C) of the core-shell elastomer (B) to the silicone (C) is 8 to 40, The resin composition is a resin composition for decorative part clip molding. 8 . Particles, which are particles of the resin composition according to claim 1 , 2 or 7 .

9. A molded article formed from the resin composition according to claim 1, 2 or 7.

10. A molded article formed from the pellets according to claim 8. The molded article according to claim 9 , which is a decorative buckle.

Citation Information

Patent Citations

  • Glass melting equipment

    JP1988210036A

  • Automobile interior part

    JP2015074724A

  • Polyacetal resin composition and polyacetal resin molded article

    JP2017025257A

  • Polyacetal resin composition and molding

    JP2020132662A

  • Resin composition and molded article

    JP2021011562A